The Influence of The Physical Work Environment on Worker Productivity in Krupuk SMEs in Sidoarjo - Boy Isma Putra; Cholifah; Ghozali Rusyid Affandi (Journal of Research and Technology, 2023)
This study aims to examine the influence of the physical work environment of cracker factory workers in Sidoarjo. This study aims to find out which factors have the most influence among the factors of temperature, noise and lighting and the coloring of the work environment that are suitable for the work productivity of cracker factory workers in Sidoarjo. This research was conducted to improve the performance of Krupuk UKM workers in Gading Village, Krembung-Sidoarjo District by paying attention to a good physical work environment. The work environment is everything that exists around workers who can influence them in carrying out the tasks given. Working conditions where a good workplace includes a physical environment that can provide a sense of security, peace, and fun. The physical work environment is a work environment which includes several aspects that must be considered, these aspects include: a comfortable work space, safe environmental conditions, constant room temperature, adequate lighting, and appropriate room paint colors, so that a productivity result is achieved optimal work. The data analysis used in the study used the SPSS program aid with the linear regression method. The results of the study are the significance value of the correlation between productivity as measured through the completion time of the milling section and noise (dB) which has a significant correlation value of 0.364; productivity with lighting (lux) has a significant correlation value of 0.141 and productivity with temperature (OC) has a significant correlation value of 0.168. This proves that productivity has a strong relationship with noise (dB) with a significant correlation value of 0.364. The solution implemented to maintain work productivity related to noise is to provide personal protective equipment (PPE) to cover the ears, namely ear plugs or ear muffs.